Design of a microgrid for intelligent energy distribution - Arie Nawawi (2009)
Microgrid structure is an integrated energy system consists of a low-voltage distribution network with distributed energy resources, power electronic converters, storage devices and loads, operated either connected to the grid or islanded. Study of microgrid is a complex study, involving many dimensions: hardware, structure, configurations, performance and reliability, control strategies, etc.